PERSPECTIVE AND RELATIONSHIP QUESTION OF INTRACTABLE FARMER-HERDER CONFLICTS IN GHANA, AFRICA - Musah, H.; Sulemana, A.; Tseer, T. (UDS International Journal of Development, 2022)
Cultural factors underpin most of the intractable farmer-herder conflicts in Africa, as in Ghana. Nonetheless, these factors gained limited scholarly attention. This paper examines the infamous farmerherder conflict in the Asante-Akyem District of the Ashanti Region. Four hundred respondents cumulatively were randomly and purposely selected in a mixed study design. A cross-tabulation was ran to determine the extent to which differences in nationality, religion, norms, values, and stereotyping played roles in the conflict. The study found that; 94.7% of farmers, 88.7% of herders, 87.9% of middle persons’ group, and 83.3% of chiefs and cattle owners respectively, agreed that the differences in these variables are the prime cultural factors that have sustained the conflict and impeded its resolution. The study recommends a re-socialisation of Fulani herders and their host communities by conflict experts and other stakeholders through workshops to foster healthy co-existence in their diversities. Keywords: Farmer-Herders, Conflict, Cultural Variabilities, Intractability, Resolution